2003
DOI: 10.1037/0022-0167.50.1.52
|View full text |Cite
|
Sign up to set email alerts
|

Symptom improvement and length of treatment in ethnically similar and dissimilar client-therapist pairings.

Abstract: This study examined the length of treatment and degree of symptom improvement of African American, Hispanic, and Caucasian clients as a function of therapist ethnicity using data obtained from 42 university and college counseling centers over a 2-year period. When analyses were collapsed across clienttherapist ethnicity combinations, ethnic similarity was associated with a slightly longer duration of treatment. However, when a random deletion procedure was used to render the number of dyads within each ethnic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 32 publications
4
40
0
Order By: Relevance
“…Despite the potential for mistrust that can occur because of a trauma history and/or racial/ethnic differences, it appeared that patients were able to engage in their treatment and benefit from it regardless of whether they were the same race/ethnicity as their therapist. The lack of a significant association between racial/ethnic match and session attendance is consistent with previous research with outpatient substance abuse populations (Fiorentine and Hillhouse 1999; Sterling et al 1998) and university college students (Erdur et al 2003). It is also consistent with meta-analytic findings from Maramba and Hall (2002) and Shin et al (2005) suggesting racial/ethnic match may not be a clinically significant predictor of treatment retention.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Despite the potential for mistrust that can occur because of a trauma history and/or racial/ethnic differences, it appeared that patients were able to engage in their treatment and benefit from it regardless of whether they were the same race/ethnicity as their therapist. The lack of a significant association between racial/ethnic match and session attendance is consistent with previous research with outpatient substance abuse populations (Fiorentine and Hillhouse 1999; Sterling et al 1998) and university college students (Erdur et al 2003). It is also consistent with meta-analytic findings from Maramba and Hall (2002) and Shin et al (2005) suggesting racial/ethnic match may not be a clinically significant predictor of treatment retention.…”
Section: Discussionsupporting
confidence: 89%
“…Several studies found that within racially/ethnically matched dyads, patients had higher alliance ratings, reported greater understanding and acceptance of the treatment approach, and displayed more positive post-treatment outcomes compared to racially/ethnically mismatched dyads (Ricker et al 1999; Thompson and Alexandar 2006; Wintersteen et al 2005). In contrast, other studies fail to find evidence that ethnic matching leads to better treatment outcomes or greater satisfaction with therapy (Erdur et al 2003; Jones 1982). …”
Section: Introductionmentioning
confidence: 90%
“…Cohen 1989;Walsh 1989). As well, the significance of the engagement process in cross-cultural psychotherapy has been repeatedly emphasized (Cardemil and Battle 2003;Coleman 2002;Constantine 2002;Dyche and Zayas 1995;Erdur et al 2003;Keenan 2001;Keenan et al 2005;Horvath 2006;La Roche and Maxie 2003;Lee 2008;Mishne 2002;Seeley 2000;Shonfeld-Ringel 2000;Stuart 2004;Sue 2006). Engagement is seen as critical to a client's decision to continue with or drop out of treatment (Gregory and Leslie 1996;Frank et al 1987).…”
Section: Therapeutic Alliance and The Engagement Processmentioning
confidence: 99%
“…Participants had all worked with an ethnically dissimilar therapist and all reported a therapeutic benefit from therapy, as described by Jahzara; "from now … where I am now to where I was, has been really … I've come a long way with (therapist)". Quantitative studies have also suggested that client outcomes for ethnically matched and non-matched client-therapist pairings are the same (Erdur, Rude, Baron, Draper, & Shankar, 2000). A review of the use of health services by BME individuals also concluded that the communication style and manner of relating to the patient was more important than ethnicity of the provider to BME health service users (Scheppers, van Dongen, Dekker, Geertzen, & Dekkere, 2006).…”
Section: Implications Of Having An Ethnically Dissimilar Therapistmentioning
confidence: 99%
“…In the adult literature, some have found that the strength of the alliance mediates the relationship between ethnic matching of client and therapist and the therapeutic outcome (Farsimadan et al, 2007), whilst others have found no correlation between the strength of the therapeutic relationship and outcomes in adults (Mollersen, Sexton, & Holte, 2009) and adolescents receiving therapy (Erdur et al, 2000;Ricker, Nystul, & Waldo, 1999). …”
Section: Expectations Of An Ethnically Similar Therapistmentioning
confidence: 99%